Bioinformatic Analysis in Designing Mega-primer in Overlap Extension PCR Cloning (OEPC) Technique - Mardalisa, -; Suhandono, Sony; Yanti, Novi; Rozi, Fazrol; Nova, Fitri; Primawati, - (Society of Visual Informatics, 2021)
Bioinformatics has developed into an application tool for basic and applied research in the biomedical and biotechnology field. Polymerase Chain Reaction (PCR) is a common technique in the molecular area that has always involved bioinformatics science. PCR cloning techniques such as TA cloning and PCR-mediated cloning exhibit complex processes with low success rates. One easy, effective, and practical solution is to use a mega-primer with the Overlap Extension PCR Cloning (OEPC) technique. The success of PCR cloning using the mega-primer design in the OEPC technique is strongly influenced by the characteristics of the mega-primer used. Knowledge of mega-primer characteristics is one of the important factors in the success of PCR cloning. The design process for the mega-primer str promoter was characterized based on the principle of a genetic algorithm using the web-based bioinformatics tools such as ClustalW, NetPrimer, and BLAST. The success of the mega-primer construction in producing recombinant pSB1C3 vector has been confirmed by the sequencing method and the function of the reporting protein (AmilCP). DNA analysis shows a 100 % homologous sequence on the str promoter, whileÂ E. coli colonies successfully express the purplish-blue color. Mega-primer characters can save costs and time of the research by maintaining the primer parameters that provide optimal values and increase the success value of PCR cloning via bioinformatics software. Hence, implications on biological problems, especially using DNA and amino acid sequences, could solve rapidly.